Pertanggungjawaban Notaris Dalam Pembuatan Berita Acara Rapat Umum Pemegang Saham Perseroan Terbatas - Sumiany Sirait; Udin Narsudin (Postgraduate of Jayabaya University, 2016)
The existence or presence of a Notary cannot be separated from the public as the answer to the need for evidence in writing, especially in the form of authentic deeds as the evidence of acts they have committed. The method used in this study is normative juridical legal study supported by juridical empirical approach. The results of the study show that the minutes of general meeting of a limited liability company made by a Notary may be cancelled by the Court if the making process is not in compliance with the applicable regulations of law, so that the notary shall be responsible whether civilly, administratively, or in terms of Law on Position of Notary and professional code of ethics and criminally (if they are proven to have given false information/involved in committing an unlawful act).